Implementation of Good Governance in the Management of Social Educational Assistance to Students - Samad Rumalolas; Kismartini Kismartini; Faizal Madya (Husnayain Business Review, 2025)
Educational assistance for students in Fakfak Regency has not yet been implemented effectively. In the implementation of this assistance, the principles of Good Governance have not been implemented properly. The purpose of this study is to analyze the implementation of the principles of good governance and to analyze the supporting and inhibiting factors in the educational assistance program for students in Fakfak Regency. The research method used in this study is a qualitative descriptive approach. Qualitative data analysis was carried out interactively and continuously until completion, so that the data has become saturated. The results of the study revealed that the Educational Assistance Program for Students in Fakfak Regency has not been implemented in accordance with the principles of good governance, including: (a) Participation, space for the public to express aspirations is still not available, (b) Law enforcement, the form of case resolution is resolved with external intervention, (c) Transparency, the Fakfak Regency Government has not been open in this educational assistance program, (d) Responsiveness, the government's response or attention in educational assistance for students is very lacking, (e) Effectiveness and efficiency, the realization of the educational assistance program for students is below 100%, (f) Accountability, the practice of corruption, collusion and nepotism for this educational assistance is growing very well. The conclusion of the study is the implementation of good governance in the student education assistance program by opening as much space as possible for community participation. Suggestions for the future are that the Fakfak Regency Government needs to provide ample space for the community to participate in providing information. If there is a violation of the law in the management of student education assistance, then the government must take legal action. The Fakfak Regency Government must also be responsive to every aspiration or complaint, by opening an online complaint/aspiration space. The Fakfak Regency Government needs to have Standard Operating Procedures. There needs to be planning that starts from the Village Level to the Regency Level.